The EU Leniency Programme and Recidivism - Catarina Marv\~ao (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2014)
The EU Leniency Programme (LP) aims to encourage the dissolution of existing cartels and the deterrence of future cartels, through spontaneous reporting and/or significant cooperation by cartel members during an investigation. However, the European Commission guidelines are rather vague in terms of the factors that influence the granting and scale of fine reductions. As expected, the results shown that the first reporting or cooperating firm receives generous fine reductions. More importantly, there is some evidence that firms can "learn how to play the leniency game", either learning how to cheat or how to report, as the reductions given to multiple o ffenders (and their cartel partners) are substantially higher. These results have an ambiguous impact on firms' incentives and major implications for policy making.
Keywords: K21; K42; L40; L51; 330; Cartels; competition policy; Leniency Programme; self-reporting